Analysis of multiphase flow characteristics in a deepwater riser. Issue 1 (21st February 2021) - Liang, Weixing; Lou, Min
Abstract : Oil and gas mixed transportation is an important technology in oil and gas production. Multiphase fluid is transported from the wellhead to the floating platform through a riser system. Based on computational fluid dynamics, a numerical model of multiphase flow in a deepwater riser by considering hydrate phase transformation and sand production was established, which was then solved by the finite-difference method. The results show that under constant inlet pressure, the pressure drop decreases with increasing gas–liquid two-phase flow rate, and increases with increasing sand production rate. Furthermore, the hydrate phase transition decreases the pressure. The effect of liquid on the temperature in the riser is apparent: the heat transfer between the fluid and seawater is mitigated by the insulation layer, thus raising the critical point of the hydrate phase transition. Finally, the velocity and volume fraction of the gas phase increase from the inlet to the outlet of the riser. At the same time, the velocity of the liquid–solid phase increases, whereas the volume fraction decreases.